Analysis On The Effects Of Gradation Of Sand On Shear Strength Characteristics - Srigaran, Prabagaran (Universiti Sains Malaysia, 2019)
This study concentrated on gradation of sand which affects shear strength parameters significantly. This study also focusing on the effects of small and large shear boxes on different soil gradation. All tests were conducted on fully dried sand, sizes ranging from 0.063mm to 2mm. Sieve analysis is done to classify the material into fine sand, medium sand and coarse sand, while direct shear test in small and large scale were conducted to determine shear strength parameters of the samples. It was found that friction angle tend to increase as the percentage of coarse sand increases in the sample. This is due to the improved angularity and surface roughness of the coarser sand which makes the sand to be more resistant against shearing. Size of shear box has an impact on test results as friction angle decreases when larger scale of shear box is used. The decrement in friction angle is caused by space enough for the sand particles in the box to develop individual shear bands fully within the shear zone. It is proven that coarser sand has better shear strength properties and suitable to be used for the construction of geotechnical structures which will prevent failures in future. Results of larger shear box is more reliable as it gives more accurate results compared to small shear box. It will will prevent overestimation of shear strength parameters in design